(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Oral and pharyngeal cancer, grouped together, is the sixth most common cancer in the world. Oral cancer also has a significant impact on individual patient quality of life and substantial patient treatment costs, often due to late presentation when the disease is at an advanced stage. Primary prevention to increase awareness of risk factors and the early signs and symptoms for oral cancer is proposed. There is clear lack of awareness and attribution of oral malignancies and risk factors in general public. So, the study aims to assess public awareness in patients visiting a Tertiary Medical Center. MATERIALS AND METHODS: This descriptive cross sectional study was conducted in Outpatient department of Dental department at Nobel Medical College Teaching Hospital in Biratnagar, Nepal. A total of 120 participants both male and female above 18 years of age were participants in the study, consisting of smokers, non-smokers and former smokers. Data were analysed by descriptive statistics like mean and percentage. RESULTS: Out of total 120 participants, 60% belonged to age group of 18-29 years whereas 30% belonged to age group 30-40 years. 75% of the participants were married. 15% of the participants were uneducated and 40% had education upto high school. 70% of the participants had heard of oral cancer and the main source of information on oral cancer was television 45(45%) as compared to other sources of information. Out of total study subjects 75% were tobacco chewers, 55% were alcohol consumers while 75% of the study population had knowledge of early signs of oral cancer. CONCLUSIONS: This study highlights the inadequacy of knowledge about oral cancer in general population. It is highly recommended that mass media campaigns with government funded programs and private medical institutions should run oral cancer programs in timely intervals.